Topography-Aware Geospatial Digital Marketing: A Systematic Literature Synthesis of Local SEO, Spatial Targeting, and Accessibility-Driven Consumer Intent - Maria Lourdes Santos Maria Lourdes Santos; Jose Miguel Dela Cruz Jose Miguel Dela Cruz; Angela Mae Villanueva Angela Mae Villanueva (Techne: Journal of Engineering, Technology and Industrial Applications, 2025)
This article presents a systematic literature synthesis (SL) that consolidates research across digital marketing, information systems, spatial analytics, and urban studies to build an engineering-oriented understanding of how topography and geospatial constraints influence local SEO performance, location-based advertising effectiveness, and omnichannel conversion outcomes. Using a transparent SL protocol, the review organizes findings into thematic clusters: (1) geospatial signals in local search and discovery, (2) geo-targeting and geo-fencing for paid media, (3) accessibility-based segmentation and service areas, (4) place-based content strategy and location credibility, (5) measurement, attribution, and privacy constraints, and (6) operational models and decision support for topography-aware marketing. The synthesis identifies a persistent gap: limited integration of topographic friction and network travel-time into mainstream digital marketing workflows, despite strong evidence that accessibility mediates consumer intent and moderates campaign outcomes. The article proposes a conceptual framework, offers copy-ready tables for SL reporting and practice translation, and provides figure prompts for scientific visualizations suitable for Techne submissions. The resulting contribution is an applied roadmap for designing digital marketing as a location-intent system grounded in physical accessibility rather than simplistic distance, with implications for local SEO governance, media efficiency, conversion reliability, and equitable service delivery.